2011
DOI: 10.1186/1752-1947-5-300
|View full text |Cite
|
Sign up to set email alerts
|

Management of a rare case of arrhythmogenic right ventricular dysplasia in pregnancy: a case report

Abstract: IntroductionArrhythmogenic right ventricular dysplasia is a heritable disease of the heart muscle characterized by fibrofatty degeneration of cardiomyocytes. Patients present with ventricular arrhythmias or congestive heart failure, and sometimes sudden cardiac death occurs. Prenatal diagnosis has become possible with the detection of mutations, but, to the best of our knowledge, no case of prenatal diagnosis has been reported previously. There is little information about the management of arrhythmogenic right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In a case reported by Iriyama, et al, 18) the propranolol treatment that the patient had been taking was not given during the pregnancy on her own request and VT occurred at the 34 th week. Similarly in the case of Güdücü, et al, 17) the patient taking regular metoprolol and propafenone treatment for 3 years with the diagnosis of ARVC refused to use the drugs on her own request and she became symptomatic at the 32 nd week. In her Holter ECG at the 32 nd week, frequent PVC attacks were detected.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In a case reported by Iriyama, et al, 18) the propranolol treatment that the patient had been taking was not given during the pregnancy on her own request and VT occurred at the 34 th week. Similarly in the case of Güdücü, et al, 17) the patient taking regular metoprolol and propafenone treatment for 3 years with the diagnosis of ARVC refused to use the drugs on her own request and she became symptomatic at the 32 nd week. In her Holter ECG at the 32 nd week, frequent PVC attacks were detected.…”
Section: Discussionmentioning
confidence: 86%
“…[14][15][16][17][18] Therefore, it is difficult to assess the risks of pregnancy and delivery in patients with ARVC. Furthermore, sustained VT developed during the pregnancy in only one of these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case reported by Iriyama et al [18] documented that discontinuation of antiarrhythmic therapy during pregnancy may result in the development of major ventricular arrhythmias for example. On the other hand, in a case report, Güdücü et al [19] showed that discontinuation of β-blocker therapy may not compromise a successful pregnancy, even in a patient advised to take β-blocking agents to prevent arrhythmias; the patient experienced heart palpitations, and ECG Holter monitoring at the 32nd week of gestation showed >16,000 ventricular extrasystoles.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed genetic counseling about the risk of inheritance of cardiac defects for her child because genetic analysis can avoid the lifelong cardiological follow-up in the child if the mutation is not detectable [19]. This analysis cannot predict with certainty the clinical phenotype and risk stratification, because the final phenotype is also determined by incomplete penetrance and pleiotropic effects, and may vary significantly.…”
Section: Discussionmentioning
confidence: 99%